PERBEDAAN HASIL BELAJAR SISWA YANG DIAJARKAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DAN MODEL PEMBELAJARAN DISCOVERY PADA MATERI SEGITIGA DI KELAS VII SMP NEGERI 15 AMBON - Lelapary, Willyam; Palinussa, Anderson L; Huwaa, Novalin C (Universitas Pasifik Morotai, 2023)
The study aims to improve student learning about flat triangle through the student team achievement division learning model. The application of STAD, the researcher used an experimental quantitative research with a quasi experimental design. Research sample is VII5 class (using STAD) dan VII6 class (using discovery learning) at SMP Negeri 15 Ambon, Baguala Distric, Ambon City. The instrument using it essay test dan the result is analizeby descriptive statistic and inferential statistic the resultof analize show that the average student learning from VII5 class is 68,67 and average student from VII6 class is 61,39 this means that student learning using STAD model have greatly improve when compared with student learning with discovey learning model